A Sporting Nation: Creating Sámi Identity through Sport - Pedersen, Helge Christian (The International Journal of the History of Sport, 2021)
Sport and identity are closely interrelated; sport creates identity and identity creates sport. This is also the case in the development of Sámi sport, as the Indigenous Sámi population in the north of Finland, Sweden and Norway has used sport to contribute to (re)building Sámi identity for over 40 years. This sporting identity has been based on an essentialized past, portraying Sámi culture and identity as being indistinguishably linked to Sámi reindeer husbandry culture. By deploying sports such as reindeer racing, lasso throwing and cross-country skiing, the Sámi sport association has painted a picture of Sáminess as a unique identity distinctly different from Norwegian culture and identity. Gayatri Spivak uses the term strategic essentialism to explain how Indigenous people and minority groups can create and use specific historical traits and traditions in their political struggle for recognition and self-respect. Sámi sport is an example of Spivak’s theory – the Sámi sports movement has been deployed to create greater self-esteem amongst the Sámi and to promote greater political rights. The Sámi sport movement has developed a Sámi sporting identity across (at least) three intertwined dimensions: an ethnic identity dimension, a national identity dimension and an indigenous identity dimension.